PEMBERDAYAAN MASYARAKAT DI MASA PANDEMI MELALUI PELATIHAN USAHA PEMBUATAN KUE (UKM) DAN PENYUSUNAN BUKU LAPORAN KEUANGAN DI DESA PELIATAN, UBUD, BALI - Made Dian Putri Agustina; Ni Kadek Sukerni (UNHI Press, 2021)
The spread of Covid-19 not only shook the world of health (health shock) but also provided a shock to the economy (economic shock), namely almost no economic activities carried out by economic actors, be it households and company (firm). With the existence of restrictions on the mobility of the community and economic activities, in an effort to prevent the spread of this virus, which is increasingly widespread, it has an impact on consumption and production and investment activities to decrease (economy contraction). Mrs. Ayu is one of the communities affected by Covid-19. Mrs. Ayu had to be sent home due to the limited activities carried out by the company where Mrs. Ayu previously worked. Mrs Ayu also tries to find alternative businesses that can make money and can be done at home during this pandemic. Mrs Ayu also started a small business (UKM) to make gabin cakes. The problems faced are: 1) Unattractive product packaging and lack of product variation.2) Don't have a marketing system like social media. 3) Do not have a financial books and report or records related to income, expenses, production costs and profit and loss. The solutions offered for this problem are: 1) Training on production and marketing strategies which helps partners in making more attractive packaging so that they can increase marketing and make alternative gabin cakes that are more varied in taste or shape that are more contemporary; 2) Assisting partners in making social media that can assist in the product marketing process and introduce products not only to consumers in Peliatan Ubud but also marketed in the surrounding areas; 3) Assisting in making simple financial books and reports.